2004
DOI: 10.1242/jcs.01345
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intercellular communication in macrophages: possible interactions between GAP junctions and P2 receptors

Abstract: Gap junctions are connexin-formed channels that play an important role in intercellular communication in most cell types. In the immune system, specifically in macrophages, the expression of connexins and the establishment of functional gap junctions are still controversial issues. Macrophages express P2X7 receptors that, once activated by the binding of extracellular ATP, lead to the opening of transmembrane pores permeable to molecules of up to 900 Da. There is evidence suggesting an interplay between gap ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 62 publications
6
38
0
Order By: Relevance
“…While this mechanism has some experimental support (44), our data suggest that the membrane pore formation is mediated by ATP and the major mechanism is the P2X 7 R. We observed pore formation after treatment with the P2X 7 R agonist BzATP and pore formation in osteoblasts, and MLO-Y4 osteocytes was blocked with apyrase, which hydrolyzes extracellular ATP thus interrupting its signaling. Others have suggested that Cx43 and P2X 7 R might have interacting functions (45). In peritoneal macrophages, Cx43 and P2X 7 R are co-localized at the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…While this mechanism has some experimental support (44), our data suggest that the membrane pore formation is mediated by ATP and the major mechanism is the P2X 7 R. We observed pore formation after treatment with the P2X 7 R agonist BzATP and pore formation in osteoblasts, and MLO-Y4 osteocytes was blocked with apyrase, which hydrolyzes extracellular ATP thus interrupting its signaling. Others have suggested that Cx43 and P2X 7 R might have interacting functions (45). In peritoneal macrophages, Cx43 and P2X 7 R are co-localized at the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the P2X 7 R reportedly interacts with connexin-43 (CX-43) (31), another hemichannel protein linked to ATP release (32). It has been suggested that the presence of functional P2X 7 at the cell surface may facilitate membrane insertion of CX-43 and the formation of gapjunction channels between MA (31). Therefore, the possibility exists that P2X 7 -coupled Panx-1 and/or CX-43 may participate in MA-MA interaction and fusion.…”
mentioning
confidence: 99%
“…Gap-junction proteins are also known to accumulate in cholesterol-rich rafts (Schubert et al, 2002;Lin et al, 2003;Lin et al, 2004;Dunina-Barkovskaya, 2005). Connexin Cx43 is found in macrophages (Beyer & Steinberg, 1991;Beyer & Steinberg, 1993;Anand et al, 2008); colocalization of purinoreceptors P2X7 with connexin Cx43 in macrophages was reported (Beyer & Steinberg, 1991;Beyer & Steinberg, 1993;Fortes et al, 2004). Figure 1 shows the fragments of the proteins aligned versus the CRAC sequence.…”
Section: Cholesterol-binding Sites In Integral Proteins Involved In Pmentioning
confidence: 98%